Enhancing lycopene production in Bacillus subtilis by overcoming a critical enzymatic bottleneck - Rehman, Esha; Birla Singh, Hawaibam; Nguyen, Minh Phuong; Wang, Chonglong; Yoon, Sang-Hwal; Kwon, Moonhyuk; Kang, Min-Kyoung; Kim, Seon-Won (Frontiers in Bioengineering and Biotechnology, 2025)
Bacillus subtilis a Generally Recognized As Safe (GRAS) microorganism, is an attractive chassis for producing high-value compounds in a safe and sustainable way. However, its potential for producing the C40 carotenoid lycopene has been limited by inefficient precursor supply and enzyme incompatibility. This study demonstrates that lycopene production in B. subtilis can be significantly enhanced through systematic metabolic engineering by rewiring the lycopene and methylerythritol phosphate (MEP) pathways. A synthetic lycopene biosynthesis pathway expressing the crtE gene from Pantoea agglomerans, which is commonly used for microbial lycopene production, failed to yield lycopene production in B. subtilis. However, replacing crtE with a multifunctional geranylgeranyl diphosphate synthase (GGPPS) from Archaeoglobus fulgidus successfully enabled lycopene synthesis. The optimization of the fermentation medium demonstrated that a combined carbon supply of glucose and glycerol markedly enhanced both cell growth and lycopene production in comparison with separate carbon sources. To further boost production, the methylerythritol phosphate (MEP) pathway was engineered by overexpressing the rate-limiting enzyme, 1-deoxy-D-xylulose-5-phosphate synthase (dxs), which resulted in a five-fold increase in lycopene titer after 72 h. Screening of various GGPPS enzymes revealed that idsA from Corynebacterium glutamicum was the most efficient, further increasing the yield. The final engineered strain achieved a lycopene titer of 55 mg/L in shake-flask cultivation, a significant improvement over the previously reported level in B. subtilis. These results demonstrate that targeted GGPPS selection and precursor pathway engineering are critical strategies for developing B. subtilis into a robust and sustainable platform for carotenoid production.